CORPORATE GOVERNANCE DAN KECURANGAN LAPORAN KEUANGAN (STUDI EMPIRIS PADA PT DI SEKTOR REAL ESTATE DAN KONTRUKSI) - Fatiyah Amri, Fika; Puttri, Daniati (Fakultas Ekonomi dan Bisnis Universitas Bung Hatta, 2024)
This research aims to empirically test the contribution of Corporate Governance to financial report fraud, using institutional ownership, managerial ownership and the board of commissioners as independent variables. The population in this research is Real Estate and Construction companies listed on the Indonesia Stock Exchange in 2020-2022. The sample in this research was determined using purposive sampling, with the total sample obtained being 114 data sourced from 38 companies that met the sample criteria. The type of data used in this research is secondary data obtained from annual reports sourced from the official website of the Indonesian Stock Exchange and company websites. Testing was carried out using multiple linear regression analysis. The research results show that institutional ownership and managerial ownership have an effect on financial report fraud. Meanwhile, the board of comissioners variable has no effect on financial report fraud.